Knowledge and practice of planned pregnancy among married women. - Acharya, Kiran (2012)
ABSTRACT: This study was a descriptive quantitative study which was conducted with non-probability purposive sampling technique design on "Knowledge and Practice of Planned Pregnancy among married women" who came for ANC check-up in Chitwan Medical College. In the FY 2068/69 the total ANC visit number was 15185, by taking 8% allowable error the sample size became 149. The main objectives of study was to find out the knowledge of married couples on planned pregnancy and to identify the proportion of wanted and unwanted pregnancy .This study had taken about one and half months time for the data collection only due to ANC days are two days in a week. Almost all respondents were come from joint family which is 83%. Similarly, almost respondent were engaged in house work and 39% had secondary level education. Mean age at marriage for men was 23.68 years and 19.42 years for women. Fifty one percent of first pregnancy was on desire .Twenty percent mothers had faced miscarriage and 17.4% had faced abortion but which was done by Doctors and Nurses. Fifty four percent pregnancies were at the age of (15-20) years. Thirty two percent mothers had given their child birth in two years difference. Sixty-one percent had good knowledge on FP. 61% had used FP devices and 15% had used natural FP devices. Fifty seven percent had done unplanned pregnancy and 77.2% had fair knowledge on planned pregnancy. Seventy-five percent mothers had given second child birth due to the concept of "two children are necessary". Similarly 26.8% had given child birth due to the son preference. Seventy -three percent mothers had faced physical types of problems during pregnancy. Ninety-five percent mothers had said that pregnancy should on their desire. Similarly, 72% mothers had good knowledge on pre-requisites before pregnancy. In the end of the study we conclude that there is no correlation between knowledge and practice on planned pregnancy.